Вплив компонентного складу субстрату на біологічно активні речовини антиоксидантного типу в зелені базиліку - Прісс, Олеся Петрівна; Присс, Олеся Петровна; Priss, Olesia; Бурдіна, Ірина Олександрівна; Бурдина, Ирина Александровна; Burdina, Iryna (Мелітополь: ТДАТУ, 2017)
EN: Effect of substrate component composition on accumulation of biologically active substances with antioxidant properties in basil was studied. It was determined that inclusion of perlite into substrate stimulates accumulation of poliphenols, ascorbic acid, carotenoids and essential oils in basil.
Влияние компонентного состава субстрата на биологически активные вещества антиоксидантного типа в зелени базилика
Effect of the substrate composition on biologically active substances with antioxidant рroperties in basil
Keywords: субстрат; васильки; паліфеноли; аскорбінова кислота; каротиноїди; ефірна олія